Social and economic upgrading in the garment supply chain in Vietnam - Do Quynh Chi (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2020)
The textile and garment industry in Vietnam has achieved fast expansion in terms of production capacity and export value in all three areas of fibre, textile and clothing manufacturing since the early 2000s. However, the growth of the industry has been mainly attributed to the increase of labour and capital rather than economic upgrading. Most of the garment companies in Vietnam are still participating at the lowest value-added sections of global value chains. This report finds little progress in product, functional and sectoral upgrading at the production level. The reasons for the stagnation in economic upgrading originate both in the international buyers' policy to limit technology transfer to protect their business advantage and the lack of an effective industrial policy by the Vietnamese government. Social upgrading has been achieved mostly in the larger, export-oriented firms that are under the scrutiny of international buyers, while the SMEs and household businesses have been plagued with forced overtime, wildcat strikes, and low wages.
Keywords: F16; F23; L16; 330; economic upgrading; social upgrading; global value chains; industrial policy; labour rights; garment industry